Assessment of parents’ oral health related behaviours and its relationship with oral health status of the children aged between 6-12 years in Davangere city: a cross-sectional survey - D. Sharief, Gazala Sulthana; B., Sapna (International Journal Of Community Medicine And Public Health, 2024)
Background: It is widely acknowledged that the behaviour of parents affects their children's health. This study aimed to evaluate the relationship between oral health behaviour of parents and oral health status of their children aged between 6-12 years. Methods: A cross-sectional survey was conducted among 420 parent-child dyads with children aged between 6-12 years. A self-designed proforma was used for recording the sociodemographic details, with a questionnaire to assess parents’ oral health-related behaviours followed by clinical examination of the children for their oral health status. The Chi-square test, spearman’s correlation test and binary logistic regression analysis were applied by considering Statistical significance at p<0.05. Results: The majority of the parents reported of having good oral health-related behaviours (60.2%). When children’s oral health status was assessed, more than half of the children had low caries experience (62.5%), showed a milder form of gingivitis (96.2%) and good oral hygiene status (57.4%). No statistically significant association was found between parents’ oral health-related behaviours with the children’s oral health status. Conclusions: Parents’ oral health-related behaviours did not influence the children’s oral health status.